THE INTERPLAY BETWEEN CLINICAL AND LABORATORY PARAMETERS OF MOUTHESOF PATIENTS WHO DO NOT HAVE HIGH ABRASION OF HARD DENTAL TISSUES - Ткаченко, І.М. (World of Medicine and Biology, 2014)
In this article we present an algorithm for the study of clinical and laboratory parameters of the oral cavity of patients with outexisting pathology by reducing the thickness of the hard tooth tissues for comparison with the data for patients with increased wear of hard tooth tissue for accurate diagnosis in the early stages of development and selection of nosology treatment depending on the changes established by clinical – laboratory parameters. Based on the sestudies can be noted that for patients of a certainage, sex, andwith certain constitutional features observes pattern in the study of indicators that can be transferred, under certain circumstances, to the whole population. There is an algorithm of clinical and laboratory research methods, and functional methods with the establishment of digital data for the study population.